2012
DOI: 10.1371/journal.pone.0052921
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid HU210 Protects Isolated Rat Stomach against Impairment Caused by Serum of Rats with Experimental Acute Pancreatitis

Abstract: Acute pancreatitis (AP), especially severe acute pancreatitis often causes extra-pancreatic complications, such as acute gastrointestinal mucosal lesion (AGML) which is accompanied by a considerably high mortality, yet the pathogenesis of AP-induced AGML is still not fully understood. In this report, we investigated the alterations of serum components and gastric endocrine and exocrine functions in rats with experimental acute pancreatitis, and studied the possible contributions of these alterations in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…In our study, pepsin secretion was increased in pylorus‐ligated rats after stimulation of gastric acid by different secretagogue. Cao et al, who demonstrated that HU210 the CB1 agonist decreasing the secretion of gastric acid and peptic activity in the isolated rat stomach irritated by acute pancreatitis. The current work showed that treatment with NADA and AM630 reduces gastric acid secretion, decreases peptic activity and promotes mucus secretion suggesting their protective ability of mucosal membrane and facilitating ulcer healing process.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, pepsin secretion was increased in pylorus‐ligated rats after stimulation of gastric acid by different secretagogue. Cao et al, who demonstrated that HU210 the CB1 agonist decreasing the secretion of gastric acid and peptic activity in the isolated rat stomach irritated by acute pancreatitis. The current work showed that treatment with NADA and AM630 reduces gastric acid secretion, decreases peptic activity and promotes mucus secretion suggesting their protective ability of mucosal membrane and facilitating ulcer healing process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Massa F, [24] used different chemicals to induce experimental bowel inflammation, and found that colitis had been more severe in CB1 knockout mice compared to that in wild type mice. Moreover, the pretreatment of wild type mice with CB1 receptor antagonists gave rise to an up-regulated inflammatory response, while CB1 receptor agonists subdued inflammatory response [40]. Other studies also elucidated that endogenous ligands of CB1 receptors, such as anandamide (AEA), 2-arachidonoylglycerol (2–AG), and palmitoylethanolamide (PEA) were found capable of attenuating inflammation through decreasing proinflammatory cytokine release, inhibiting mast-cell degranulation and reducing edema [22], [23], [41].…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic cannabinoids can further enhance these properties. Cao et al provoked acute lesions of the gastrointestinal mucosa in rats by inducing acute pancreatitis and then showed that synthetic cannabinoid HU210, a non-selective CB agonist, reversed the morphological and serum anomalies, demonstrating its anti-inflammatory properties [78]. A later study showed that HU210 protects the intestinal mucosa in a murine model of ulcerative colitis, most likely through the toll-like receptor 4 (TLR4) and mitogen-activated protein (MAP) signaling pathways [79].…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%